Influence of Air Conditioning on the Vertical Deposition and Inhalation Risk of Indoor Microplastics - Norfatiha Ishak; Nor Ruwaida Jamian; M. Dewika; Sara Yasina Yusuf; Roshafima Rasit Ali; Nur Aqilah Samsukamal (Bumi Publikasi Nusantara, 2026)
Indoor environments are important pathways of microplastic (MP) exposure because people spend long periods indoors and are surrounded by synthetic textiles and plastic-based furnishings. This study examined how air-conditioning (AC)-induced air recirculation affects the vertical deposition and inhalation risk of MPs in a closed, furnished bedroom. Passive samplers were placed at floor level (0.2 m) and breathing height (1.2 m) under stagnant air (SA), low-temperature AC (LTA), and high-temperature AC (HTA) conditions. Results showed that AC transformed the indoor atmosphere from a settling-dominant to a recirculating-suspension state. Under SA, larger MPs (>500 µm) settled mainly to the floor, whereas AC increased MP deposition at breathing height and redistributed particles into the inhalation zone. Smaller fractions (<100 µm) and more diverse polymers, including polypropylene, polystyrene, and polyvinyl acetate, were also detected under AC operation. Overall, AC may improve comfort while unintentionally increasing indoor inhalation exposure to MPs.